2003
DOI: 10.1038/sj.onc.1207056
|View full text |Cite
|
Sign up to set email alerts
|

Role of promoter methylation in regulation of the mammalian heparanase gene

Abstract: Mammalian heparanase (endo-b-glucuronidase) degrades heparan sulfate proteoglycans and is an important modulator of the extracellular matrix and associated factors. The enzyme is preferentially expressed in neoplastic tissues and contributes to tumour metastasis and angiogenesis. To investigate the epigenetic regulation of the heparanase locus, methylation-specific and bisulfite PCR were performed on a panel of 22 human cancer cell lines. Cytosine methylation of the heparanase promoter was associated with inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 68 publications
(90 reference statements)
2
88
0
Order By: Relevance
“…This is best demonstrated in Raji cells that lack intrinsic heparanase activity ( Fig. 1E) (20), whereas tumor xenografts produced by these cells exhibit typical heparanase activity. The ability of mAbs 9E8 and H1023 to attenuate the growth of these tumors (Figs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is best demonstrated in Raji cells that lack intrinsic heparanase activity ( Fig. 1E) (20), whereas tumor xenografts produced by these cells exhibit typical heparanase activity. The ability of mAbs 9E8 and H1023 to attenuate the growth of these tumors (Figs.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the lack of heparanase activity in Raji cells (Fig. 1E, Upper, Raji cells) because of gene methylation (20), tumor xenografts produced by Raji cells exhibit typical heparanase activity (Fig. 1E, Upper, Raji tumor), suggesting that heparanase-positive cells derived from the host populate the tumor microenvironment.…”
Section: Inhibition Of Heparanase Originating From the Tumor Microenvmentioning
confidence: 99%
“…Heparanase expression in bladder cancer T Ogishima et al treatment, suggesting that promoter methylation could be involved in the transcriptional regulation of the heparanase gene (Shteper et al, 2003). Based on the functional promoter sequence of heparanase gene (De Mestre et al, 2003), MSP and USP primers were specifically designed to analyse the difference in promoter CpG methylation between normal bladder and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the prevalence of genome-wide hypomethylation has been described in several cancers (Kaneda et al, 2004) and site-specific hypomethylation of the promoter region has been shown to upregulate the expression of cancer-promoting genes (Ehrlich, 2002). Recently, promoter methylation has been associated with the regulation of heparanase expression in cancer cell lines (Shteper et al, 2003). In addition to the active involvement of promoter methylation in heparanase regulation, early growth response 1 (EGR1), a member of the zinc-finger family of transcription factors, has been shown to be important in the inducible transcription of the heparanase gene (De Mestre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Induced heparanase expression under pathological conditions suggests a transcriptional regulation. Heparanase gene expression has been shown to involve promoter methylation (22), eukaryotic initiation factor 4E (23), and the Ets (24) and Egr1 (25) transcription factors. Recently, estrogen has been shown to induce heparanase promoter activation in estrogen receptor-positive breast cancer cells (26).…”
mentioning
confidence: 99%